Mengapa Siswa SMP di Indonesia melakukan Perundungan? : Menelusuri Faktor-Faktor Penyebab Kekerasan di Sekolah - Mohammad Sholihul, Wafi (Pustaka Peradaban, 2024)
Bullying is an aggressive behavior that has become a significant issue among junior high school students in Indonesia. This study employed a literature review method to identify the underlying reasons behind this phenomenon. To provide a comprehensive explanation, this study examined three primary perspectives: peers, school environment, and parental influence, to answer the research question,